Silicon application mitigates abiotic stresses in rice: A review - JINGER, DINESH; DEVI, MOIRANGTHEM THOITHOI; DHAR, SHIVA; DASS, ANCHAL; SHARMA, V K; S, VIJAYA KUMAR; JOSHI, EKTA; JATAV, HANUMAN SINGH; SINGH, NEELAM (The Indian Journal of Agricultural Sciences, 2020)
Rice (Oryza sativa L.) is the paramount staple crop, providing food to more than 50% people globally. Although, India has attained the apex position in producing rice after China, however, its productivity is still below the world’s average productivity due to several physical abiotic and chemical stress. Silicon (Si) is a multipurpose element that acts as a panacea for multiple stresses. Rice is a heavy accumulator (200–300 kg Si/ha) of Si. Addition of Si prevents movement of heavy metals and salts through cell wall (apoplastic) eventually decreasing their uptake, particularly when rice face iron (Fe) and manganese (Mn) toxicity and increase the rice yield by 20.5–72.7%. Studies have revealed that application of Si mitigates arsenic (As) stress in rice by diminishing its uptake and improving the antioxidants activities. Foliar application of Si increases rice production by 30% under As and cadmium (Cd) contamination conditions. Besides, Si reduces transpiration in rice crop by 30% and also eliminates the effect of heat stress (42.5oC). Further, application of Si in rice has been shown to increase culm strength, integrity and stability of vascular bundle thus, preventing crop against lodging. These review results clearly reveal the importance of Si in imparting abiotic stress tolerance and need for its application in rice crop.